Legal Frameworks and Dispute Resolution Mechanisms in Indonesia's Fintech Sector: A Normative Analysis - Febrian, Saputra I. Y.; Napitupulu, Diana RW (Research Horizon, 2025)
This paper examines the effectiveness of legal frameworks and regulations in Indonesia’s fintech sector, focusing on consumer data protection, dispute resolution, and law enforcement. The study analyzes key regulations, including POJK No. 13/2018, SEOJK No. 14/SEOJK.07/2014, UU ITE No. 11/2008, and PBI No. 22/20/PBI/2020, to evaluate their role in safeguarding consumer data and managing digital transactions. Using a qualitative, descriptive analysis, the research highlights that these regulations establish strong foundations for data security, requiring fintech companies to implement robust security systems such as encryption and access control. However, the study also identifies gaps in enforcement, especially concerning the oversight of regulatory bodies like OJK and Bank Indonesia. Additionally, the research finds that while legal provisions are in place, there is a lack of accessible dispute resolution mechanisms for consumers, which could undermine trust in the fintech sector. The study concludes that improvements are needed in both the enforcement of these regulations and the accessibility of dispute resolution options. These findings emphasize the importance of ensuring effective legal frameworks and stronger regulatory oversight to foster a secure and trustworthy fintech environment.